The return of a forgotten harvestman: revalidation of Gonyleptes robustus Holmberg, 1876, as the second species of Acanthopachylus Roewer, 1913 (Arachnida, Opiliones, Gonyleptidae) - Acosta, Luis E. (Zootaxa, 2021)
Gonyleptes robustus Holmberg, 1876 (Opiliones, Gonyleptidae), hitherto under the synonymy of Acanthopachylus aculeatus (Kirby, 1819) is revalidated. It is recognized as the second species of genus Acanthopachylus Roewer, 1913, currently monotypic, giving the new combination Acanthopachylus robustus (Holmberg, 1876) comb. nov. The huge synonymy formerly assigned to A. aculeatus is split among the newly identified entities. Diagnostic differences (male exomorphology) that underlie the taxonomic and nomenclatural decision are succinctly displayed. Brief historical references to the arachnological work of Eduardo L. Holmberg are also given.